Doutor, não consigo ver! Um caso de cegueira cortical bilateral - Hugo M Oliveira; João Massano (Sociedade Galega de Medicina Interna, 2014)
Cortical blindness is defined as a loss of vision secondary to lesions of the striate cortex in the occipital lobes. The most common cause of cortical blindness is occipital lobe infarction in the vascular territory of the posterior cerebral arteries (PCA). Unilateral occipital infarction is not uncommon, but bilateral occipital infarction is a rare phenomenon. We present a case of a 70-year-old man with a history of hypertension presented to the emergency department with sudden onset of bilateral visual loss and dizziness for 4 hours. He denied any other neurological symptoms. There was no history of trauma or migraine. The patient's blood pressure was 170/85 mmHg, pulse rate was 70 beats/min and regular. Pupillary light reflex and accommodation reflex were normal. Fundus examination revealed normal optic discs and neurological examination was unremarkable. Blood tests were within normal range. Urgent cerebral computed tomography scan showed questionable right occipital cortico-subcortical hypodensity. Cerebral magnetic resonance (figure 1) revealed bilateral ischemic lesions involving both posterior cerebral artery territories. Further investigations, including cardiac monitoring, echocardiography and carotid doppler ultrasound, were normal. Six months later the patient was diagnosed with atrial fibrillation. PCA infarction occurs most often secondary to emboli from the heart or vertebrobasilar circulation. The aetiology of the infarction cannot be determined in at least 25% to 38% of patients. Bilateral occipital infarction, although rare, is a medical emergency and should be considered an important differential diagnosis for sudden onset bilateral blindness.